(2x+5)+(2x-23)=90

Simple and best practice solution for (2x+5)+(2x-23)=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+5)+(2x-23)=90 equation:


Simplifying
(2x + 5) + (2x + -23) = 90

Reorder the terms:
(5 + 2x) + (2x + -23) = 90

Remove parenthesis around (5 + 2x)
5 + 2x + (2x + -23) = 90

Reorder the terms:
5 + 2x + (-23 + 2x) = 90

Remove parenthesis around (-23 + 2x)
5 + 2x + -23 + 2x = 90

Reorder the terms:
5 + -23 + 2x + 2x = 90

Combine like terms: 5 + -23 = -18
-18 + 2x + 2x = 90

Combine like terms: 2x + 2x = 4x
-18 + 4x = 90

Solving
-18 + 4x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 4x = 90 + 18

Combine like terms: -18 + 18 = 0
0 + 4x = 90 + 18
4x = 90 + 18

Combine like terms: 90 + 18 = 108
4x = 108

Divide each side by '4'.
x = 27

Simplifying
x = 27

See similar equations:

| .6x+-1.3=x | | 3cotx=5 | | 3(4r-7)-4(r-1)= | | ln(x^2-3x)=0 | | (3x+35)+(5x-15)=180 | | 5z+3z=7z-3 | | 6x+x-8=6x+2 | | -5w+4w+3=-9 | | 5v-12=33 | | (2x+26)+(6x-10)=180 | | 3*(2x-4)+5=4x+11 | | -11=-17v | | 8=9-8-6 | | 8x+3y= | | 3*x+7=2*(8+x) | | (x+55)+(4x+25)=180 | | 11y=-8 | | 1.8s-2=4.3 | | x-0.75x=185 | | -2(x-7)-20=6 | | 36=8+0.7x | | x^2+y^2-x-4y+4=0 | | (Y*11)+Y=156 | | 25=8.2m-16 | | 5.6+3p=20 | | y=3(1/3)-2 | | 19=4z-13.8 | | 5/(5x^2-1)=1/(x-1) | | 4j+16=98 | | x/4+4.7=8.2 | | hg(9)=3.08sqrt(9)+18.97 | | (k+1)(k+2)(k+3)=k^3+6k^2+11k+6 |

Equations solver categories